2018
DOI: 10.1093/tas/txy070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breed and castration on production and carcass traits of male lambs following an intensive finishing period

Abstract: The practice of crossbreeding using a terminal sire and the use of intact rather than castrated animals has the potential to increase the productivity of lambs produced from the hill sheep sector. The objective of this study was to compare the production and carcass characteristics of purebred Scottish Blackface (SB) and Texel cross Scottish Blackface (TXSB) ram and wether lambs fed on a concentrate diet and slaughtered at different ages. Two hundred spring born male lambs (average birth age ± SD 9.53 d) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
6
21
4
Order By: Relevance
“…Purebred lambs had significantly lower daily gains compared with Texel crossbreds which agrees with results of this study. As in our study, Claffey et al (2018) observed that crossbreds with Texel had significantly higher carcass weights, dressing percentages, and carcass conformation scores than purebred lambs. In their study, Texel crossbreds had significantly lower carcass fat scores than purebred Scottish Blackface lambs, while the present study found no difference in subcutaneous fat and internal fat between purebred JSR lambs and crossbreds with Texel.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Purebred lambs had significantly lower daily gains compared with Texel crossbreds which agrees with results of this study. As in our study, Claffey et al (2018) observed that crossbreds with Texel had significantly higher carcass weights, dressing percentages, and carcass conformation scores than purebred lambs. In their study, Texel crossbreds had significantly lower carcass fat scores than purebred Scottish Blackface lambs, while the present study found no difference in subcutaneous fat and internal fat between purebred JSR lambs and crossbreds with Texel.…”
Section: Discussionsupporting
confidence: 85%
“…These results are similar to findings of the present study, where crossbreds with Texel were ranked in the U-class, while purebred lambs were categorized in class R-. Claffey et al (2018) also used Texel rams as the terminal breed for commercial crossbreeding. They compared growth and carcass traits of purebred Scottish Blackface lambs and crossbreds with Texel.…”
Section: Discussionmentioning
confidence: 99%
“…The lower DM (and subsequent nutrient) intake in Mule ewes compared to both Belclare X and Lleyn X ewes reported in the current study aligns with Arnold [35] who reported that Leicester X ewes had lower OMD intake per kg of BW than Merino and Dorset horn ewes. The dams of the Mule ewes in the current study were Scottish blackface, which Claffey et al [36] reported had lower intakes (kg FW) compared to Scottish blackface × Texel lambs. Regarding the findings from the current study, Arnold [35] and Claffey et al [36] suggest that Mule ewes are genetically predisposed to lower feed intakes compared to other breed types.…”
Section: Feed and Nutrient Intakementioning
confidence: 60%
“…The dams of the Mule ewes in the current study were Scottish blackface, which Claffey et al [36] reported had lower intakes (kg FW) compared to Scottish blackface × Texel lambs. Regarding the findings from the current study, Arnold [35] and Claffey et al [36] suggest that Mule ewes are genetically predisposed to lower feed intakes compared to other breed types. However, the performance of the Mule ewes remained similar for both BW and BCS compared to the other breed types, which had increased feed intake.…”
Section: Feed and Nutrient Intakementioning
confidence: 60%
“…Recent studies have outlined the superior growth rate and feed conversion of Texel cross Scottish Blackface ( SB ) ( TXSB ) ram and wether lambs compared with purebred SB ram and wether lambs ( Claffey et al, 2017 ). In Ireland, hill lambs (lambs from mountain regions) require an intensive feeding period to achieve 16- to 22-kg carcasses required for current market specification ( Diskin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%